Supplementary file 1_The role and mechanism of p53 F229V mutation in inhibiting pseudorabies virus replication.docx - Cuilian Yu (6264992) (2025)
The p53 protein is a key transcription factor that regulates cellular responses to stress and is widely recognized as a host restriction factor against various viral infections. However, its specific role in pseudorabies virus (PRV) replication, pathogenesis, and host response remains unclear. This study identified a swine p53 (sp53) mutation in the PK15 cell line under prolonged passage stress, characterized by an amino acid substitution at position 229, replacing phenylalanine with valine (sp53 F229V). This mutation eliminates the transcriptional activity of wild-type p53 and confers resistance to PRV infection. Notably, it reverses p53’s original pro-viral role, converting it into an inhibitor of PRV proliferation. Further analysis revealed that the PRV early protein EP0 promotes the degradation of sp53 F229V through the proteasome pathway. These findings indicate that a defined p53 alteration can decouple transcriptional and antiviral functions in a mutation-specific, context-dependent manner. The EP0–p53 interface emerges as a candidate target to modulate PRV replication, pending validation. These findings were obtained in vitro and require in vivo validation in pigs to determine their relevance to PRV pathogenesis.